PROJECT-BASED LEARNING AS AN INNOVATIVE APPROACH TO DEVELOPING 21ST CENTURY SKILLS IN EFL CLASSROOMS (Ustozlar uchun, 2025)
Project-Based Learning (PBL) has emerged as an effective learner-centered approach that promotes active engagement, critical thinking, collaboration, and real-world problem-solving. This article examines the role of PBL in developing 21st century skills among students learning English as a Foreign Language (EFL) in Academic Lyceums. The study is based on theoretical analysis of contemporary pedagogical literature and classroom observations. The findings suggest that PBL enhances learners’ communicative competence, creativity, digital literacy, and autonomy. The article concludes that integrating PBL into EFL instruction contributes significantly to improving educational outcomes and preparing students for future academic and professional challenges.